Identifikasi Tumbuhan Paku Sejati (Filicinae) di Curug Ciparay Desa Cidugaleun, Kecamatan Cigalontang Kabupaten Tasikmalaya - Ega Saputra Unsil; Muhammad Rizky Fauzan; Raisul Muslim; Indra Gunawan; Esta Rendra RS (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study aims to identify and analyze the diversity of true ferns (Filicinae) in Curug Ciparay, Desa Cidugaleun, Tasikmalaya Regency, a region with significant potential for botanical research due to its supportive microclimatic conditions, including high humidity and cool temperatures. Using a descriptive qualitative method, involving direct observation, documentation, and interviews, the study identified 15 species of true ferns in the area, with species distribution influenced by variations in microhabitats, especially humidity and lighting. These ferns contribute not only to biodiversity but also play essential ecological roles in maintaining soil moisture, preventing erosion, and providing habitats for small fauna. The findings underscore the importance of conservation efforts involving the local community to protect the ecosystem from human activities, such as tourism. This study is expected to serve as a foundation for conservation strategies and sustainable management in Curug Ciparay.